Caracterização tecnológica de caulinitas e avaliação do potencial do rejeito de beneficiamento da caulinita como fertilizante mineral - Região de Equador/RN - Sousa, Joel Pedrosa (2024)
In the region of Equador, in the State of Rio Grande do Norte, there occur an extensive swarm of pegmatites which belong to the Borborema-Seridó Pegmatitic Province. This study involves a mapping conducted in an area of 63 km² and the characterization of kaolins in the region of Equador and adjacencies. Within a broader geological context, the study site is inserted in the Borborema Province, in the Rio Grande do Norte Domain, in the Seridó Group. Three formations of the Seridó Group were identified: Jucurutu, Equador and Seridó Formations.The pegmatites are classified as homogeneous, however, in the study area, they exhibit compositional zoning. At least two generations of pegmatite were found, one occurring in the kaolin deposits and another in a sharp contact completely preserved. In the petrographic analysis, plagioclase, feldspar, quartz, and muscovite were identified. The structures generated in the rocks underwent ductile deformation, accounting for the formation of banded structures, marked by the orientation and mineral recrystallization, foliation, stretching and folds. The brittle deformation is typified by fractures and veins filled by quartz-feldspathic and argillaceous materials. The occurrences of kaolin are associated with the alteration of feldspar forming the pegmatites, presenting quartz and muscovite fragments along with kaolin. The Atterberg limits demonstrate differences between the 100 and 200 mesh samples, highlighting the importance of the separation process for the purity of processed kaolin. The presence of other planar minerals influences the plasticity of the material, leading to variations in its industrial exploitation. The results obtained from the X-Ray diffraction analysis (XRD) were kaolinite (kln), quartz (qtz), muscovite (msc), microcline (mic) and, in one of the samples, spodumene (esp). The Scanning Electron Microscope (SEM) analyses, as well as those of Energy Dispersive Spectroscopy (EDS), contributed to the correlation between the chemical composition and morphology of the minerals identified in the analysed samples. Kaolin minerals, muscovite, fragments of quartz, altered feldspars and iron oxide/hydroxides were noted. From the observations made in the electron microscopy it was possible to consider the possibility of the exploitation of the waste resultant from the kaolin beneficiation as an agricultural remineralizer, since the presence of muscovite and potassium feldspars undergoing alteration may favor the bioavailability of potassium for plants.